What makes me stay in teaching? exploring retention factors of TVET teachers in Malaysia - Omar, Muhd Khaizer; Mat Rashid, Abdullah; Mohd Puad, Mohd Hazwan (Science and Engineering Research Support Society, 2019)
Generally, teaching is regarded as a reputable profession among different communities. In particular, the teaching profession is alluring not for its dignified status but the nature ofits profession, which is to ‘teach’. Indeed, many religions have highlighted that a teacher is able to deliver people from darkness and provide enlightenment in the form of knowledge. With respect to this fact, the significance of the teaching profession in the community and society is undeniable. In order to comprehend the reasons of Malaysian Technical and Vocational Education and Training (TVET)instructors retaining in the teaching profession, the researchers in this study have employed a mixed-method design by applying a convergent parallel design of which both qualitative and quantitative data were combined into a single instrument. For this article, the researchers explored the TVET teachers’ qualitative narration by analyzing the open-ended feedback gathered from the online survey. In specific, an online-survey formnamed Qualtrics was utilized to collect the research data. Besides, Telegram, an online social networking application, was used as a platform for teachers to access the link to the online open-ended questions. To note, retention in this context refers to TVET teachers who have served more than ten years in the TVET institutions. Also, an expert was hired to ensure the validity of the narrative provided by the instructors. For the purpose of thematic analysis, Atlas.ti was utilized. Essentially, the findings that emerged from the analysis provided insight to improve retention of TVET teachers. Further connection to the Motivation-Hygiene theory that served as the theoretical foundation was also established in this study. While the role of TVET teachers to develop adroit future workforce among the grassroots of the nation is apparent, it is vital for the factors of their retention to be clearly understood. Subsequently, this measure will ensure the teaching quality and motivation to teach continue to remain as the paramount agenda in the TVET system. In this study, the researchers have taken into consideration the ‘teacher’s voice’ in order to acknowledge their effort and to spur their interest in the profession.